La gestión logística y la gestión administrativa en la empresa Af Boullosa EIRL, periodo 2023 - Rodriguez Guerra, Laura Tatiana (2024)
Logistics management, as well as administrative management, comprise a set of actions developed by the company and that mainly articulate activities such as: planning, organizing, controlling, directing and distributing; all of them oriented so that it can meet the objectives and goals established in relation to a specific period. The research carried out is titled "Logistics management and administrative management in the company AF Boullosa EIRL, period 2023", the study focuses mainly on determining the relationship between the study variables (logistics management and administrative management). The research follows a quantitative type with a descriptive correlational design, the survey and the questionnaire were used as a collection technique and instrument, the relevance of the instrument was achieved through the reliability test, which was applied to a population of 35 individuals. Likewise, the study shows an intense positive relationship according to the result obtained through the Pearson correlation coefficient, which was 0.821, that is, a very high correlation and a degree of significance 0.000.